Investigation of the system AgIn5S8-FeIn2S4 - I. V. Bodnar; T. H. Barugu (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The single crystals of FeIn2S4, AgIn5S8 compounds and (FeIn2S4)1- x AgIn5S8 solid solutions have been grown with Bridgeman method. Their composition and structure were determined. It is seen that the pointed compounds and solid solutions are crystallized in the spinal cubic structure. The elementary cell parameters calculated with the least square method change linearly. The density of FeIn2S4, AgIn5S8 compounds and their solid solutions were calculated with the pycnometric method. The density and the elementary cell parameter with х compasitions change linearly. The temperatures od phase transformation were determined with the differential thermal analysis and the diagram of the AgIn5S8-FeIn2S4 system state was built.